Mayan People Within and Beyond Boundaries : Social Categories and Lived Identity in the Yucatan. - Hervik, Peter (Taylor and Francis, 2013)
Mayan People Within and Beyond Boundaries explores the Maya of Yucatan, the Maya of academic institutions and the Maya of the tourist industry. It examines the interplay between the local and the external, academic categories of the Maya, and seeks to transcend the paradoxical and incongruent relationship between the social spaces that breathe life into the categories. The notion of ""shared social experience"" is introduced to embody a focus on reflexivity that goes beyond the subjective position of the author and helps demystify the coexisting subjectivities characteristic of ethnog.